Polycapillary based µXRF station for 3D colour tomography - Hampai D. Darjyush; Cherepennikov Yu. M. Yuriy Mihaylovich; Liedl A. Andrea; Cappuccio G. Giorgio; Capitolo E.; Iannarelli M.; Azzutti C. Claudia; Gladkikh Yu. P. Yulia Petrovna; Marcelli A. Augusto; Dabagov S. B. Sultan Barasbievich (2018, 2018)
Title screen